1984
DOI: 10.1093/schbul/10.4.624
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Outcome Using Broad (DSM-II) and Narrow (DSM-III) Concepts of Schizophrenia

Abstract: The classical prognostic indicators of Vaillant and Stephens, the acute onset of psychotic symptoms, and key demographic factors were investigated as predictors of outcome in a prospective study of 153 schizophrenic patients defined using broad (DSM-II) and narrow (DSM-III) concepts of schizophrenia. Findings indicate: Several established prognostic items did not show strong predictive utility in DSM-II or DSM-III schizophrenia when young, nonchronic patients were studied. For both DSM-II and DSM-III schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 41 publications
3
44
1
2
Order By: Relevance
“…Thus there are multiple potential factors which could influence posthospital work functioning for patients with schizophrenia, and these were assessed. These include prehospital work history, prehospital social adjustment, education, marital status, acute onset, precipitating events, and blunted affect from the scales of Vaillant and Stephens (Vaillant, 1962; Vaillant, 1978; Westermeyer and Harrow, 1984; Stephens et al, 1997), and the scales of Zigler (Zigler and Glick, 2001), as well as posthospital positive symptoms and posthospital negative symptoms. The goal was to control or parcel out the combined influence of these factors when studying work functioning over time in medicated vs unmedicated patients with schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus there are multiple potential factors which could influence posthospital work functioning for patients with schizophrenia, and these were assessed. These include prehospital work history, prehospital social adjustment, education, marital status, acute onset, precipitating events, and blunted affect from the scales of Vaillant and Stephens (Vaillant, 1962; Vaillant, 1978; Westermeyer and Harrow, 1984; Stephens et al, 1997), and the scales of Zigler (Zigler and Glick, 2001), as well as posthospital positive symptoms and posthospital negative symptoms. The goal was to control or parcel out the combined influence of these factors when studying work functioning over time in medicated vs unmedicated patients with schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…The first scale is from the studies of Vaillant (Vaillant, 1962; Vaillant, 1978) and Stephens (Westermeyer and Harrow, 1984; Stephens et al, 1997). It assesses the influence of prognostic characteristics related to later outcome for schizophrenia patients.…”
Section: Methodsmentioning
confidence: 99%
“…Validity measures were also calculated and, as expected, were adequate (see below and Table 2 ). Because socio-demographic variables have been found to modulate the prognosis of schizophrenia (Westermeyer and Harrow, 1984; Wieselgren et al, 1996), discriminant validity was assessed across categories of age, education and disease duration, and found to be robust (Supplementary Table 5). …”
Section: Resultsmentioning
confidence: 99%
“…Clinical psychiatry has traditionally defined recovery based on symptoms and several dimensions of function (service-based, objective, or clinical recovery – SBR), while consumer movements advocate for recovery to be defined as the process that involves overcoming mental illness, regaining self-control and establishing a meaningful and fulfilling life (customer-based, subjective, or personal recovery – CBR) (Schrank and Slade, 2007). In patients suffering from schizophrenia, recovery has many predicting factors, including socio-demographic variables, among others (Westermeyer and Harrow, 1984; Wieselgren et al, 1996). Specifically, age and functional status at onset, better cognitive functioning at stabilization, shorter duration of psychosis and early remission seem to best predict functional SBR (Robinson et al, 2004; Lambert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found significant associations between thought disorder and outcome as well as personality and outcomes, however, these are only a few of the many potential variables which may influence outcome. Functioning is also likely to be related to a number of factors such as symptom profile, environmental factors, and personal history (Pogue-Geile & Harrow 1985;Westermeyer & Harrow, 1984). Future work should focus on disentangling the intricate relations between personality, thought disorder, and outcomes.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%